Damage Mechanism Analysis and Preventive Measures of the Stalled Permanent Magnet Synchronous Motor in Electric Vehicle - CHEN Huimin (Kongzhi Yu Xinxi Jishu)
It analyzed the failure damage of a 150 kW permanent magnet synchronous motor for electric vehicles parked on the slope at the start, discussed the operation mechanism of permanent magnet synchronous motor under stalled conditions, and proposed a method to pre-prevent stalled damage. The running result of prototype vehicle verified the effectiveness of this method.